Actinomycetes as Xylanase Producers: A Pathway towards Sustainable Future - Mrunal K. Bhatt; Swati B. Khunt; Unnati B. Yagnik; Mousumi B. Das (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
Lignocellulosic biomass serves as a renewable raw resource. There has been increased industrial interest in leveraging this raw material through the advancement of new technologies. Various microbial enzymes interact with biomass to generate the desired products under optimal industrial conditions. Xylanases play a crucial role in breaking down the xylosidic bonds within the Xylan backbone of the biomass, and commercial enzymes are classified into distinct glycoside hydrolase families. Through genetic engineering, optimized xylanases can be developed: a novel xylanase is extracted from an extreme environment and subsequently genetically altered to enhance its applicability in industrial settings. Recombinant protein methods have enabled the engineering and production of thermostable xylanases in Actinomycetes. It has been tried to explore the biotechnological potential of xylanases derived from Actinomycetes and the techniques used for their optimization and expression in industrial applications.